The Adobe Photoshop Elements 11 book for digital photographers - Kelby, Scott (Voices that matter., 2013)
This book (for Windows and Mac) breaks new ground by doing something for digital photographers that's never been done before-it cuts through the bull and shows exactly "how to do it." It's not a bunch of theory; it doesn't challenge readers to come up with their own settings or figure things out on their own. Instead, it tells readers flat-out which settings to use, when to use them, and why. This book gives the inside tips and tricks of the trade for organizing, correcting, editing, sharpening, retouching, and presenting photos like a pro. Readers will be absolutely amazed at how easy and effective these techniques are-once they know the secrets. This book covers: -The real secrets of how the pros retouch portraits -How to color correct any photo without breaking a sweat -How to use Camera Raw for processing not only RAW photos, but JPEGs and TIFFs, too! -The sharpening techniques the pros really use -How to deal with common digital camera image problems, including removing noise and avoiding halos -The most requested photographic special effects -All the brand new features of Elements 11, which offers better ways to manage photos, map images, share memories, use templates, and easily create pro-quality photographic effects And the book's secret weapon: It also covers slick workarounds, cheats, and some fairly ingenious ways to replicate many Photoshop CS6 features from right within Elements 11. -And much more!